Neural circuits containing olfactory neurons are involved in the prepulse inhibition of the startle reflex in rats - Niu, Haichen; He, Xiaobin; Zhou, Ting; Shi, Xi; Zhang, Qiang; Zhang, Zhijian; Qiao, Yuehua; Xu, Fuqiang; Hu, Min (Frontiers in Behavioral Neuroscience, 2015)
Many neuropsychiatric disorders, such as schizophrenia, have been associated with olfactory dysfunction and abnormalities in the prepulse inhibition (PPI) response to a startle reflex. However, whether these two abnormalities could be related is unclear. The present investigations were designed to determine whether theblockage of olfactory sensory input by zinc sulfate infusion in the olfactory naris (0.5 ml, 0.17 M, ZnE) can disturb the PPI response. Furthermore, a bilateral microinjection of lidocaine/MK801 in the olfactory bulb (OB) was administered to examine whether the blockage of olfactory sensory input could impair the PPI response. To identify the neural projection between olfaction and PPI-related areas, trans-synaptic retrograde tracing with the recombinant pseudorabies virus (PRV) was used. Our results demonstrated that blockage of olfactory sensory input could disturb olfactory behavior. In the function studies, we demonstrated that blockage of olfactory sensory input could impair the pre-pulse inhibition of the startle response following decreased c-Fos expression in relevant brain regions during the PPI responses. Furthermore, similar and more robust findings indicated that blockage of olfactory sensory input by microinjection of lidocaine/MK801 in the OB could impair the PPI response. In the circuit-level studies, we demonstrated that trans-synaptic retrograde tracing with PRV exhibited a large portion of labeled neurons in several regions of the olfactory cortices from the pedunculopontine tegmental nucleus (PPTg). Thus, these data suggest that the olfactory system participates in the PPI regulating fields and plays a role in the pre-pulse inhibition of the startle response in rats.